MIKROPLASTIK DALAM SALURAN PERNCERNAAN IKAN DI WADUK JATIGEDE - Radityani, Fitri Afina; Pratiwi, Niken Tunjung Murti; Kamal, Mohammad Mukhlis; Iswantari, Aliati; Wulandari, Dwi Yuni; Panggabean, Grin Tommy; Ayu, Inna Puspa; Sakina, Edna (JURNAL PERIKANAN DAN KELAUTAN, 2025)
Jatigede Reservoir receives water masses and materials from the Cimanuk River, such as nutrients, sediments, and waste, including microplastics. This study aims to analyze the presence of microplastics in the digestive tract of caught fish in Jatigede Reservoir. Fish samples were obtained from fishermen, fish collectors, and fish farmers. Microplastic observations were carried out in the stomach and intestines of fish through the stages of observing fish eating habits, extraction, followed by FTIR analysis to determine the presence, abundance, and type of polymer. Carnivorous fish have the highest amount of microplastics. There is a marked difference between the amount of microplastics and the origin of fish intake. The shorter the fish's gut, the greater the amount of microplastics found. Based on their shape, the type of microplastic is dominated by fibers with a blue color. The most common polymer found is nylon. The digestive tract of fish in Jatigede Reservoir already contains microplastics of various types and colors, with varying amounts, according to the nature of eating fish.